An electrogenic redox loop in sulfate reduction reveals a likely widespread mechanism of energy conservation. Issue 1 (December 2018) - Duarte, Américo; Catarino, Teresa; White, Gaye; Lousa, Diana; Neukirchen, Sinje; Soares, Cláudio; Sousa, Filipa; Clarke, Thomas; Pereira, Inês
Abstract The bioenergetics of anaerobic metabolism frequently relies on redox loops performed by membrane complexes with substrate- and quinone-binding sites on opposite sides of the membrane. However, in sulfate respiration (a key process in the biogeochemical sulfur cycle), the substrate- and quinone-binding sites of the QrcABCD complex are periplasmic, and their role in energy conservation has not been elucidated. Here we show that the QrcABCD complex ofDesulfovibrio vulgaris is electrogenic, as protons and electrons required for quinone reduction are extracted from opposite sides of the membrane, with a H+ /e− ratio of 1. Although the complex does not act as a H+ -pump, QrcD may include a conserved proton channel leading from the N-side to the P-side menaquinone pocket. Our work provides evidence of how energy is conserved during dissimilatory sulfate reduction, and suggests mechanisms behind the functions of related bacterial respiratory complexes in other bioenergetic contexts. The bacterial complex QrcABCD plays a key role in the bioenergetics of sulfate respiration. Here, Duarte et al. show that this complex is electrogenic, with protons and electrons required for quinone reduction being extracted from opposite sides of the membrane.